The faith of the psychiatrist - Cook, Christopher C.H. (Mental health, religion & culture, 2011)
Research suggests that spirituality and religion are significant variables contributing to mental well-being and that they can also play an important part in the treatment of mental disorders. The present paper reviews studies which show that psychiatrists are less likely than their patients to report religious affiliation. While mental health service users report that they wish spirituality to be addressed during their treatment, psychiatrists appear to be more divided as to whether spiritual or religious matters should be addressed within routine clinical enquiry and treatment planning. However, psychiatric practice itself might be understood as requiring a kind of faith, albeit not religious, within which basic principles of clinical care are accepted by virtually all psychiatrists. It is also clear that explicit religious faith (of the patient and the psychiatrist) does potentially have an important impact on the clinical consultation, whether for good or for ill. There is a need for guidelines to govern the ways in which this impact might most effectively be managed, both ethically and therapeutically.